Perencanaan Mitigasi Bencana Banjir Non-Struktural Di Daerah Aliran Sungai Comal Hilir, Jawa Tengah - Yunus Aris Wibowo; Lintang Ronggowulan; Dian Adhetya Arif; Rikki Afrizal; Yaskinul Anwar; Ayu Fathonah (Geography Education Study Program, Universitas Kanjuruhan Malang, 2019)
Abstract: River flooding has become a serious disruption for community which lives in downstream area of a watershed. Comal Watershed is annually experience river flooding caused by Comal River. Therefore, it is necessary to proper mitigation planning. This study organized the arrangement of river flooding non-structural mitigation planning. Qualitative approach was used in this study; not to mention the research design utilzed literature study and field survey. Literature study was used for finding out the river flood events record and affected area in downdstream area of Comal Watershed. Meanwhile, field survey was conducted to overview the socio-cultural condition of the community which live in it. The results indicated that river flooding non-structural mitigation planning area in downdstream area of Comal Watershed consisted of spatial planning in harmony with landuse management of Comal Watershed, detection and prediction of the Comal River discharge conditions through recording and observing hydrometeorological data, management planning of riparian zone, Disaster literacy toward schools and community, community communication system improvement, local wisdom enhancement, evacuation route arrangement, early warning system utilization, disaster simulation and reforestation. Mitigation planning is not only the responsibility of the government, but requires awareness and cooperation from the community.